NEGARA ADIL MAKMUR DALAM PERSPEKTIF FOUNDING FATHERS NEGARA INDONESIA DAN FILOSOF MUSLIM - Khalik, Abu Tholib (Fakulta Ushuluddin dan Humaniora Universitas Islam Negeri Walisongo Semarang, Indonesia, 2016)
Abstract: This article elaborates on the concept of a fair and prosperous among the Indonesian founding fathers with the Muslim philosophers. Basic concepts of the founding fathers is Pancasila in which there is the word ‘fair’. The word ‘fair’ is also a very serious discussion among Muslim philosophers. The Muslim philosophers underlined that fair is one of the basics of leadership exemplified by the Prophet Muhammad while leading the people of Madina multi-ethnic and multi-religious, and this of course is relevant to the context of Indonesia's multi-religious, multi-ethnic and multi-class. For founding fathers, desire to create a fair society and a prosperous lofty ideals and key for the Indonesian nation. Therefore, they feel how much suffering people of Indonesia as a nation occupied by foreign interchangeably. In the occupation of Indonesia was treated unfairly, and natural wealth confiscated. This goal was already thought by the Muslim philosophers. Therefore, in comparing the two is where the significance of the concept of a just and prosperous one. Abstrak: Artikel ini akan mengelaborasi konsep negara adil dan makmur antara founding fathers (Para Pendiri Bangsa) Indonesia dengan para para filosof Muslim. Asas konsep founding fathers adalah Pancasila yang di dalamnya terdapat kata adil. Kata adil juga menjadi pembahasan yang sangat serius di kalangan filosof Muslim. Para filosof Muslim menggarisbawahi bahwa adil merupakan salah satu asas kepemimpinan yang diteladankan oleh Nabi Muhammad saat memimpin masyarakat Madinah yang multi-agama, dan ini tentu saja relevan dengan konteks Indonesia yang multiagama, multi-etnik, dan multi-golongan. Bagi founding fathers, keinginan mewujudkan masyarakat yang adil dan makmur merupakan cita-cita luhur dan utama bagi bangsa Indonesia. Sebab, mereka merasakan betapa menderitanya bangsa Indonesia ketika dijajah oleh bangsa asing yang silih berganti. Dalam penjajahan itu bangsa Indonesia diperlakukan tidak adil, dan kekayaan alam dirampas. Keinginan seperti ini ternyata sudah pula menjadi pemikiran para filosof Muslim. Karena itu, di sinilah signifikansi membandingkan kedua konsep adil dan makmur tersebut.